From Lexical Database to intelligent vocabulary trainers - Cornelia Tschichold (Cahiers du CENTAL, 2010)
Computer-assisted language learning needs better lexical databases in order to produce better softwarefor vocabulary learning. This paper attempts to give some guidelines for the construction of adedicated lexical database for vocabulary learning purposes.